The Comparative Efficacy of Non-ergot Dopamine Agonist and Potential Risk Factors for Motor Complications and Side Effects From NEDA Use in Early Parkinson's Disease: Evidence From Clinical Trials - Wu, Chunxiao; Guo, Hongji; Xu, Yingshan; Li, Luping; Li, Xinyu; Tang, Chunzhi; Chen, Dongfeng; Zhu, Meiling (Frontiers in Aging Neuroscience, 2022)
Background/Objectives: Nonergot dopamine agonist (NEDA) are recommended as the first-line treatment for patients with early Parkinson’s disease (PD) because of their efficacy in treating PD motor symptoms. However, systematic evaluations of the risk of motor complications induced by NEDA and risk factors potentially associated with motor complications are still lacking. Methods: Medline, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science were searched for potentially eligible randomized controlled trials. The incidence of motor complications, impulsive-compulsive behaviors and adverse events and clinical disability rating scale (UPDRS) scores were evaluated using standard meta-analytic methods. Metaregression was conducted on the incidence of motor complications (dyskinesia) with treatment duration and NEDA dose as covariates. Results: Patients treated with NEDA had significantly lower UPDRS total scores, motor scores and activity of daily living(ADL) scores than those receiving a placebo (WMD -4.81, 95% CI -6.57 to -3.05; WMD -4.901, 95% CI -7.03 to -2.77; WMD -1.52, 95% CI -2.19 to -0.84, respectively). Patients in the NEDA and NEDA+Levodopa (LD) groups had lower odds for dyskinesia than patients in the LD group (OR=0.21, 95% CI: 0.15-0.29; OR=0.31, 95% CI 0.24-0.42, respectively). Metaregressions indicated that the mean LD dose of the NEDA group increased, and the odds of developing dyskinesia increased (p=0.012). However, the odds of developing dyskinesia in the NEDA group were not related to treatment duration (p=0.308). PD patients treated with NEDA or NEDA+open LD had a lower risk of wearing-off implications than those treated with LD (all p<0.05). No significant difference was found between the NEDA and placebo groups in impulsive-compulsive behavior development (p>0.05). Patients in the NEDA group were more likely to suffer somnolence, edema, constipation, dizziness, hallucinations, nausea and vomiting than those in the placebo or LD group. Conclusion: NEDA therapy reduces motor symptoms and improves ADLs in early PD. The odds of developing motor complications were lower with NEDA than with LD, and dyskinesia increased with increasing LD equivalent dose and was not influenced by NEDA treatment duration. Therefore, long-term treatment with an appropriate dosage of NEDA might be more suitable than LD for early PD patients.